The effectiveness of agrobusiness technical training and education model for the field agricultural extension officers - Kristiyo Sumarwono; S. Sukardi; Soenarto Soenarto (Jurnal Pendidikan Vokasi, 2017)
The study was to: (1) find the most effective agrobusiness technical training and education model for the Field Agricultural Extension Officers to be implemented; and (2) to identify the knowledge level, the highest agrobusiness skills and the strongest self-confidence that might be achieved by the participants through the implemented training and education patterns. The study was conducted by means of experiment method with the regular pattern of training and education program as the control and the mentoring pattern of training and education program as the treatment. The three patterns of training and education programs served as the independent variables while the knowledge, the skills and the self-confidence served as the dependent variables. The study was conducted in three locations namely: the Institution of Agricultural Human Resources Development in the Province of Yogyakarta Special Region (Balai Pengembangan Sumber Daya Manusia Pertanian Daerah Istimewa Yogyakarta – BPSMP DIY); the Institution of Agricultural Human Resources Empowerment (Balai Pemberdayaan Sumber Daya Manusia Pertanian – BPSDMTAN Soropadan Temanggung Provinsi Jawa Tengah) in Soropadan, Temanggung, the Province of Central Java; and the Institution of Training and Education in Semarang, the Province of Central Java (Badan Pendidikan dan Pelatihan Semarang Provinsi Jawa Tengah). The study was conducted to all of the participants who attended the agrobusiness technical training and education program and, therefore, all of the participants became the subjects of the study. The study was conducted from October 2013 until March 2014. The results of the study showed that: (1) there had not been any significant difference on the knowledge and the skills of the participants who attended the regular pattern in training and education programs and those who attended the mentoring pattern in training and education programs; (2) the regular pattern in training and education programs and the mentoring pattern in training and education programs had significant difference on the field agricultural extension officers' self-confidence (t count = - 2.28; p = 0.03) and (t count = - 2.41; p = 0.02); and (3) the mentoring pattern in training and education programs showed very significant difference on the agrobusiness skills (t count = - 4.94; p = 0.00). The mentoring pattern in training and education programs showed significant changes in improving the field agricultural extension officers' skills and confidence for about 9.43% and 7.75% respectively in implementing the agrobusiness activities compared to the other patterns of training and education programs.